2017
DOI: 10.11114/jets.v5i4.2164
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management in Pre-service Teachers’ Teaching Practice Demo Lessons: A Comparison to Actual Lessons by In-service English Teachers

Abstract: The pre-service teachers find the chance to practice their classroom management skills during their practicum as they present demo lessons under supervision of their university instructors and mentor teachers. It had been discovered in a previous study, however, that the interactional features during the classroom management episodes in pre-service teachers' demo lessons were different from those in the lessons of the in-service teachers. The aim of this study was to unveil how pre-service teachers manage thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Related to Korkut (2017), who stated that classroom management is not only about how to control the class but also how the teacher can inspire and motivate the students, this study reveals that the student teachers can perform adequately in this teaching practicum. They can control the class, as well.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Related to Korkut (2017), who stated that classroom management is not only about how to control the class but also how the teacher can inspire and motivate the students, this study reveals that the student teachers can perform adequately in this teaching practicum. They can control the class, as well.…”
Section: Discussionmentioning
confidence: 67%
“…Based on that, the teachers are required to be able to combine all the components. The teacher has to be able to choose the best technique and strategy in teaching, also inspire and motivate the learners (Korkut, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Classroom management is a key aspect of effective teaching and learning. This assertion is supported by [23], [24], who postulate that classroom management is the central element of every teacher's daily professional experience. The findings of this theme show that pre-service teachers are unable to manage their classes.…”
Section: Discussionmentioning
confidence: 96%
“…Indicators of a well-managed classroom are that instructional groups are used effectively, and transitions between activities and management of materials and supplies are skilfully done to maintain momentum and maximize instructional time (Danielson, 2013). The research on pre-service teachers' competence in classroom management indicates that it is not only an ongoing concern to them, but that if these pre-service teachers do not master the required skills in managing classroom learning, then problems certainly escalate, leading to even more serious consequences (Pereira & Gates, 2013;Korkut, 2017). An implication of these findings for program planners and instructors, it might be suggested that pre-internship courses such as classroom management, micro teaching and field experience are needed to be added in the teacher preparation program so that the teacher candidates have the chance to improve classroom management skills in both simulation context and in the real classrooms.…”
Section: Conclusion and Discussionmentioning
confidence: 99%